THE OBLIGATION TO PROVE IN ADMINISTRATIVE COURTS IS UNDER THE RESPONSIBILITY OF THE ADMINISTRATIVE BODY AND THE OFFICIAL WHO ACCEPTED IT - Yusuf Saidazimov (International Scientific and Current Research Conferences, 2021)
In this thesis, it is stated that the duty to protect and prove the rights and legitimate interests of interested persons in the sphere of administrative law in the Republic of Uzbekistan is the responsibility of the administrative body and the official of the administrative body adopted by the committee.